PENGARUH SERVICE QUALITY, SOCIAL MEDIA ACTIVITY, DAN SERVICESCAPE TERHADAP CUSTOMER SATISFACTION RELOAD BYHP - Zoel Hutabarat (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
The growth of members at a fitness center during the pandemic did not significantly impact. The pandemic has made people more aware of the importance of health. Therefore, this study wanted to see the effect of service quality, social media activity, and servicescape on customer satisfaction at the Reload Byhp fitness center membership in Senopati, Jakarta. This study uses quantitative research methods with the census method because the number of Reload Byhp members is only 260. The questionnaires distributed were submitted with a google form via social media. The results of this study indicate a positive and significant effect of the service quality variable on customer satisfaction. The social media activity and servicescape variables positively and significantly impact customer satisfaction. These results show that members of Reload Byhp, in addition to getting excellent service, also more for easy access from the office, making it easier for members to exercise every day. In addition, public figures at the fitness center are a magnet for members to build networking while exercising.